Facile and Ecofriendly Fluorination of Graphene Oxide - Yadav, Santosh Kumar; Lee, Jin Hong; Park, Hun; Hong, Soon Man; Han, Tae Hee; Koo, Chong Min (WILEY-V C H VERLAG GMBH, 2014)
A one-pot, facile and ecofriendly approach to the fabrication of covalently fluorinated graphene using mild reaction conditions is reported. This straightforward and efficient strategy allows fluorine groups to be covalently and stably anchored onto graphene to produce single-layer functionalized graphene sheets from a graphene oxide precursor.
Keywords: SHEETS